The Cost of Urban Waste Management: An Empirical Analysis of Recycling Patterns in Italy - Cialani, Catia; Mortazavi, Reza (Frontiers in Sustainable Cities, 2020)
We investigate the Italian waste management system at municipal level, in which the separate and recycling waste collection costs represent a critical issue. The Italian setting is featured by high pressure to reach the European Union Waste Directive long-term objectives in terms of recycling waste, as well as to improve the waste management performance (UE Directive, 2008/98/CE). The empirical literature on waste management has devoted much more attention to demand-side aspects (discourage land disposal and encourage recycling and recovery) than to supply-side issues such as the cost analysis of the waste management. This paper aims to contribute in this field of research by estimating the cost function of Italian municipalities that provided waste collection and recycling services during years 2011-2017. Specifically, we estimate cost elasticity, marginal costs and economies of scale for urban recycling waste. Our findings suggest that recycling would not imply a considerable increase in total costs for most of the municipalities therefore, recycling should be encouraged. The results of this study provide insights into cost structure of recycling that may lead to a more efficient waste management.